Parameter Optimization of Frequency Selective Surfaces Made of Composite Materials - Abdullah Oğuz Kızılçay (Sakarya Üniversitesi Fen Bilimleri Enstitüsü Dergisi)
Debye model is used for approximating the frequency dependent complex effective permittivity of the composite structures in filter and shielding applications at microwave frequencies. In debye model, desired shielding effectiveness (SE) is obtained by determining the Debye parameters using trial and error method. But this may result in wasting time or not converging to an optimum solution. In this work to overcome this problem Debye parameters were optimized by using Differential Evolution (DE) algorithm. A Maxwell Garnett (MG) mixing rule was applied to these optimized parameters to obtain frequency selective surface (FSS) parameters. 12dB shielding threshold was chosen between 0.05 – 5GHz frequency range. In accordance with the obtained parameters of FSS, a structure was designed in CST simulation software and simulations had been conducted to obtain SE results. It was seen that the results obtained from analytical computations agree with those obtained from simulations.